Speech behaviour of a media personality: analysis of Olga Buzova’s communication strategies - Shmeleva Anastasia Sergeevna; Shushmarchenko Ekaterina Alexandrovna (Studia Humanitatis)
The article studies the speech portrait and analyses the communication strategies of Olga Buzova in various media formats. In the context of global digitalization and mediatisation of all spheres of social life, there is a need for comprehensive study of speech behaviour of public figures who have significant impact on mass audiences. The phenomenon of media personality acquires special significance in this context, since public figures become not only translators of communicative models but also active participants in formation of new speech practices which influence linguistic and cultural processes in society. Modern media discourse is characterised by fundamentally new forms of communication, integration of verbal and non-verbal components, mixture of institutional and personal aspects. This requires the development of comprehensive methodological approaches to its study.